A successful pregnancy following SEM fine tuning of hormonal priming - Murphy Christopher R; Adams Susan M (BMC, 2001)
Abstract Background Manipulation of the uterine epithelium utilising standard dose exogenous oestrogen (E2) and progesterone (P4) has been shown to achieve a mature secretory morphological response. However, in an in vitro fertilisation (IVF) setting, frozen embryo transfer (ET) has had a low success rate. We propose that in patients with previously failed ET attempts, the uterine epithelium can be directly visualised by biopsy and Scanning Electron Microscopy (SEM) and that with an individualised fine tuning of the hormone supplementation regime, based on the SEM examination of sequential uterine biopsies, it is possible to provide a uterine environment conducive to successful ET. Methods A 47 year old women was chosen for endometrial biopsy, histopathological dating and endometrial observation utilising SEM to determine the integrity of her secretory uterine epithelium because of her age and several previously failed attempts at frozen ET. Exogenous E2 and P4 supplementation was administered in modified doses according to the SEM result, in consecutive cycles until the epithelial response appeared satisfactory for potential implantation. Results This case study demonstrates the dramatic change in epithelial characteristics that can be achieved as a response to these altered doses of E2 and P4. The uterine morphology changed from a hypotrophic to a mature, receptive epithelium such that ET resulted in the birth of healthy twin boys. Conclusion The comparison between the consecutive biopsies in direct response to the SEM analysis and tailored modification of E2 and P4 dose clearly demonstrates, in this case, the effectiveness of individual morphological monitoring to maximise the successful outcome of ET.